2018
DOI: 10.3961/jpmph.18.027
|View full text |Cite
|
Sign up to set email alerts
|

The Pyramid of Injury: Estimation of the Scale of Adolescent Injuries According to Severity

Abstract: ObjectivesDue to their developmental characteristics, adolescents have a higher probability than other age groups of experiencing injuries caused by accidents, violence, and intentional self-harm. The severity and characteristics of injuries vary by the intentionality and mechanism of injury; therefore, there is a need for a national-level estimate of the scale and the severity of injuries in adolescents that takes these factors into account.MethodsBy using data from the Emergency Department-based Injury In-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Wadman MC [11] believed that according to the lethality of the injury mechanism, injury data will lead to 3 different pyramid types, with an inverted pyramid indicating high-lethality injuries (C), a rectangular pyramid indicating mid-level-lethality injuries (B), and a typical pyramid indicating low-lethality injuries (A). The ratio of injury pyramid of self-harm/suicide among South Korean youth was 1:7:15 [10] , showing a steep pyramid (type C); this was similar to the injury pyramid of self-harm/suicide among children and adolescents in Zhuhai City (1:3:20), indicating that self-harm/suicide had considerable lethality. The drowning injury pyramid was in the shape of an inverted triangle, indicating that, for every outpatient/emergency department injury visit that occurred, there were 1.3 injury hospitalizations and 2 injury deaths.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Wadman MC [11] believed that according to the lethality of the injury mechanism, injury data will lead to 3 different pyramid types, with an inverted pyramid indicating high-lethality injuries (C), a rectangular pyramid indicating mid-level-lethality injuries (B), and a typical pyramid indicating low-lethality injuries (A). The ratio of injury pyramid of self-harm/suicide among South Korean youth was 1:7:15 [10] , showing a steep pyramid (type C); this was similar to the injury pyramid of self-harm/suicide among children and adolescents in Zhuhai City (1:3:20), indicating that self-harm/suicide had considerable lethality. The drowning injury pyramid was in the shape of an inverted triangle, indicating that, for every outpatient/emergency department injury visit that occurred, there were 1.3 injury hospitalizations and 2 injury deaths.…”
Section: Discussionmentioning
confidence: 56%
“…Similar to the injury pyramid (1:36:1014) described by Lee [9] for children and adolescents ≤19 years old living in Massachusetts, USA, Ballesteros [44] also found that every injury death among children in the United States was accompanied by approximately 1,000 injury-related outpatient/emergency department visits. Compared with the injury pyramid for South Korean adolescents (1:162:492) [10] , for every injury death, the percentage of injury hospitalizations of children and adolescents in Zhuhai City was small, while the proportion of outpatient/emergency department visits was high. This difference may be due to different medical guarantees in different countries, and China may have a relatively heavy burden of hospitalization costs, which limits hospitalizations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Wadman MC [11] believed that according to the lethality of the injury mechanism, injury data will lead to 3 different pyramid types, with an inverted pyramid indicating high-lethality injuries (C), a rectangular pyramid indicating mid-level-lethality injuries (B), and a typical pyramid indicating low-lethality injuries (A). The ratio of injury pyramid of self-harm/suicide among South Korean youth was 1:7:15 [10] , showing a steep pyramid (type C); this was similar to the injury pyramid of self-harm/suicide among children and adolescents in Zhuhai City (1:3:20), indicating that self-harm/suicide had considerable lethality. The drowning injury pyramid was in the shape of an inverted triangle, indicating that, for every injury death that occurred was accompanied by 0.7 injury hospitalization and 0.5 outpatient/emergency injury visit.…”
Section: Discussionmentioning
confidence: 56%
“…Similar to the injury pyramid (1:36:1014) described by Lee [9] for children and adolescents ≤19 years old living in Massachusetts, USA, Ballesteros [[xxx]] also found that every injury death among children in the United States was accompanied by approximately 1,000 injury-related outpatient/emergency department visits. Compared with the injury pyramid for South Korean adolescents (1:162:492) [10] , for every injury death, the percentage of injury hospitalizations of children and adolescents in Zhuhai City was small, while the proportion of outpatient/emergency department visits was high. This difference may be due to different medical guarantees in different countries, and China may have a relatively heavy burden of hospitalization costs, which limits hospitalizations.…”
Section: Discussionmentioning
confidence: 84%